1998
DOI: 10.1161/01.cir.97.8.716
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Improves Endothelial Dysfunction in Atherosclerosis

Abstract: Cyclooxygenase-dependent, endothelium-derived vasoconstrictor release modulates acetylcholine-induced peripheral vasodilation in patients with atherosclerosis. Improvement of endothelial dysfunction with aspirin may improve vasodilation, reduce thrombosis, and inhibit progression of atherosclerosis and provides a pathophysiological basis for the beneficial effects of aspirin in atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(159 citation statements)
references
References 53 publications
6
150
1
2
Order By: Relevance
“…Investigation of possible mechanisms, by which low-dose aspirin can influence on BP of patients with AH and hypercholesterolaemia Improvement of endothelial function was shown in acute studies, 28,29 while results of chronic trials are conflicting [30][31][32] Our study demonstrates that addition of low-dose aspirin in hypertensive and hypercholesterolaemic subjects on top of antihypertensive and statins improves endothelial function and reduces BP Homogeneity of the studied population. Demonstration of synergistic interactions between aspirin and statins on BP reduction via improvement of NOmediated endothelial function Small study.…”
Section: Low-dose Aspirin On Bp In Hypertensive Patientsmentioning
confidence: 72%
See 1 more Smart Citation
“…Investigation of possible mechanisms, by which low-dose aspirin can influence on BP of patients with AH and hypercholesterolaemia Improvement of endothelial function was shown in acute studies, 28,29 while results of chronic trials are conflicting [30][31][32] Our study demonstrates that addition of low-dose aspirin in hypertensive and hypercholesterolaemic subjects on top of antihypertensive and statins improves endothelial function and reduces BP Homogeneity of the studied population. Demonstration of synergistic interactions between aspirin and statins on BP reduction via improvement of NOmediated endothelial function Small study.…”
Section: Low-dose Aspirin On Bp In Hypertensive Patientsmentioning
confidence: 72%
“…[23][24][25][26][27] It is of note that low-dose aspirin, at least in acute studies, improves endothelial function in patients with hypercholesterolaemia 28 and atherosclerosis. 29 Results of chronic trials are conflicting. [30][31][32] Since other COX inhibitors showed no beneficial vascular effects, aspirin might exhibit a vasculoprotective, COX-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The subject of pharmacological treatment of endothelial dysfunction has been reviewed by myself and others recently (52,94,95). Suffice it to say, interventions associated with favourable cardiovascular outcomes have been associated with attenuation of endothelial dysfunction for the most part (96)(97)(98)(99)(100)(101). The notable exception to this is hormone replacement therapy, which has been associated with improvement in endothelium-dependent vasomotion, but not cardiovascular outcome.…”
Section: Relationship Of Endothelial Function To Risk Factors and Thementioning
confidence: 99%
“…Anti-inflammatory therapies, including nonselective and selective COX inhibitors, have been reported to improve endothelial function in patients with risk factors and established atherosclerosis. For example, aspirin (Husain et al 1998) and the selective COX-2 inhibitor celecoxib (Widlansky et al 2003b) have both been shown to improve endothelium-dependent dilation. It is well established that cholesterol-lowering therapy also reduces systemic markers of inflammation, including CRP (Ballantyne et al 2003).…”
Section: Human Studies Of Systemic Inflammation and Endothelial Dysfumentioning
confidence: 99%